The enterprisation process and the discourse of the entrepreneurial university: An analysis of the Pelotas Federal University (UFPel) - Franz, Alice Hübner; Leite, Elaine da Silveira; Rodrigues, Marcio Silva (Education Policy Analysis Archives, 2020)
This article aims to discuss the growing influence that the business model has had on humans and their organizations, a consequence of a process called world's enterprisation. In this study, we opted for a look at the university, from the analysis of a specific discourse that, with the neoliberalism intensification, has been strongly disseminated: the discourse of the entrepreneurial university. From this perspective, sought to problematize how the enterprisation process has influenced the construction of the discourse of the entrepreneurial university at the Pelotas Federal University (UFPel), from the realization of a qualitative research, descriptive, which used the case study as a technique. The results from the analysis of the managers' perceptions and practices evidenced at UFPel, show that the entrepreneurial university discourse is based on different discursive practices that make constant reference to the enterprise knowledge-power. This practices reinforce the need to consolidate a flexible and efficient university (in enterprising terms), whose performance should foster innovation and economic development, by encouraging the creation of new businesses, new products or any solution that can transform knowledge into something that generates value. <!–[if !supportLineBreakNewLine]–> <!–[endif]–>